2017
DOI: 10.1093/eurheartj/ehx700
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil for improving outcomes in patients with corrected valvular heart disease and persistent pulmonary hypertension: a multicenter, double-blind, randomized clinical trial

Abstract: AimsWe aimed to determine whether treatment with sildenafil improves outcomes of patients with persistent pulmonary hypertension (PH) after correction of valvular heart disease (VHD).Methods and resultsThe sildenafil for improving outcomes after valvular correction (SIOVAC) study was a multricentric, randomized, parallel, and placebo-controlled trial that enrolled stable adults with mean pulmonary artery pressure ≥ 30 mmHg who had undergone a successful valve replacement or repair procedure at least 1 year bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
134
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(145 citation statements)
references
References 32 publications
(54 reference statements)
1
134
0
10
Order By: Relevance
“…Importantly, there is no evidence for a beneficial effect of PAH‐specific therapies for the management of patients with PH due to left heart disease; the opposite may even be the case . Very recently, a randomized trial evaluating the effect of the phosphodiesterase‐5 inhibitor sildenafil in patients with persistent PH several months after valve replacement/repair (median mPAP 39 mmHg, median PVR 3.4 WU) found worse clinical outcomes (death, hospital admission, worsening functional class, global symptom burden) in patients treated with sildenafil compared to placebo . The study included patients with both IpcPH and CpcPH but the effect of sildenafil was similar in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, there is no evidence for a beneficial effect of PAH‐specific therapies for the management of patients with PH due to left heart disease; the opposite may even be the case . Very recently, a randomized trial evaluating the effect of the phosphodiesterase‐5 inhibitor sildenafil in patients with persistent PH several months after valve replacement/repair (median mPAP 39 mmHg, median PVR 3.4 WU) found worse clinical outcomes (death, hospital admission, worsening functional class, global symptom burden) in patients treated with sildenafil compared to placebo . The study included patients with both IpcPH and CpcPH but the effect of sildenafil was similar in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Recent examples include the ENABLE and MELODY-1 studies, showing that the two ERAs bosentan and macitentan failed to improve clinical measures or outcome in patients with HFrEF or HFpEF, respectively, and in both studies ERA therapy was associated with an increased occurrence of fluid retention [91,92]. In addition, the SIOVAC trial has shown that the use of sildenafil was associated with an increased risk of clinical deterioration and worse outcome versus placebo in patients with PH after VHD intervention (aortic, mitral, or tricuspid) [93], thus indicating that such therapies may even be harmful in the context of LHD. When viewed together, there is currently no new evidence that would justify the general use of PAH therapies in PH-LHD, and potentially harmful effects have to be considered.…”
Section: Targeted Pah Therapy In Ph-lhdmentioning
confidence: 99%
“…43 Recently, the SIOVAC trial results reported worse outcomes with sildenafil in patients with persistent PH after correction of valvular disease. 44 These last two studies suggest that sildenafil's induced lung vasodilatation increased pulmonary venous return and LV filling pressure causing haemodynamic damage to a flow-sensitive failing heart. Furthermore, sildenafil might also lead to hypoxemia in CHF by increasing ventilation-perfusion mismatching.…”
Section: Medical Interventionsmentioning
confidence: 99%
“…However, the most important randomized trial that tested the administration of PDE5‐I (sildenafil) in 216 patients with HFpEF for 24 weeks did not show any improvement in exercise capacity or clinical status . Recently, the SIOVAC trial results reported worse outcomes with sildenafil in patients with persistent PH after correction of valvular disease . These last two studies suggest that sildenafil's induced lung vasodilatation increased pulmonary venous return and LV filling pressure causing haemodynamic damage to a flow‐sensitive failing heart.…”
Section: Do the Various Definitions Of Post‐capillary Pulmonary Hypermentioning
confidence: 99%